Efficient upgrading of CO to C3 fuel using asymmetric C-C coupling active sites - Xue Wang (Nature Portfolio, 2019)
Catalysts for CO electroreduction have focused on Cu, and their main products have been C2 chemicals. Here authors use the concept of asymmetric active sites to develop a class of doped Cu catalysts for C-C coupling, delivering record selectivity to n-propanol.